(untitled) (REMUNOM, 2025)
Introduction: The introduction of mobile devices in schools has transformed education, offering instant access to information and new forms of interaction. However, this insertion has also generated challenges, such as difficulty concentrating and impacts on students’ mental health. Objective: To investigate the effects of hyperconnectivity and its impacts on public policy formulation for basic education. Method: This is a theoretical essay based on a critical review of the existing literature on the use of technologies in education and their impacts on mental health. Studies were developed that discuss the relationship between the use of mobile devices, concentration and emotional well-being, as well as educational policies related to restricting the use of cell phones. Results and Discussion: The results indicated that, although restricting the use of cell phones in schools contributed to greater student concentration and improved academic performance, it also caused symptoms of digital withdrawal, such as irritability, anxiety and difficulties adapting. It was highlighted that the combination of pedagogical strategies that promote focus and the development of socio-emotional skills is essential to mitigate these adverse effects. Final Considerations: The ban may be academically effective, but the psychological impacts must be taken into account, requiring the implementation of strategies that favor the emotional well-being of students, such as activities that promote adaptation to the absence of mobile devices and the strengthening of emotional skills.